2014
DOI: 10.1007/s10897-014-9742-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Deaf Awareness Training: Knowledge and Attitudes of Recent Genetic Counseling Graduates

Abstract: Research suggests that when healthcare providers lack cultural competence, minority groups, including the Deaf community, are adversely affected. Although most genetic counseling programs incorporate cultural competency training into their curricula, the extent and impact of Deaf awareness training is unknown. The purpose of this study is to assess Deaf awareness training of recent graduates and its impact on knowledge of deafness and Deaf culture, and attitudes toward deaf people. Genetic counselors who gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…A survey of recently graduated genetic counselors showed 77% had no, or minimal training. 6 There are few descriptions of DHH training in medical school. 7,8,9 None are recent and the wider uptake of these interventions remains unknown.…”
Section: Concerns Have Led To Calls For Improved Deaf Cultural Competmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of recently graduated genetic counselors showed 77% had no, or minimal training. 6 There are few descriptions of DHH training in medical school. 7,8,9 None are recent and the wider uptake of these interventions remains unknown.…”
Section: Concerns Have Led To Calls For Improved Deaf Cultural Competmentioning
confidence: 99%
“…Published examples come from North America and the United Kingdom. A survey of recently graduated genetic counselors showed 77% had no, or minimal training 6 . There are few descriptions of DHH training in medical school 7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Providers who lack or rate low in cultural competence in working with Deaf patients may further perpetuate community and individual histories of inadequate care and poor treatment adherence. 9,10 In a 2017 smoking and lung disease study of 188 Deaf adults aged 55 to 80 years, Deaf patients who did not experience accessible communication with their doctors were significantly less likely to ask about lung cancer screening testing compared with Deaf patients who used ASL or other sign language interpreters to communicate with their health care providers. 6 However, in another national study of nearly 300 LGBTQ-identified Deaf adults, the presence of a sign language interpreter in the room did not appear to increase patients' disclosure of their marginalized sexual orientation and/or gender identities (SOGIs) to health care providers.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In practice, studies have highlighted that healthcare pro-fessionals, such as pharmacists and pharmacy students, have low knowledge about deafness and deaf culture. [10][11][12] Consequently, patients' low health literacy, along with with pharmacists' inadequate communication skills and lack of training, can cause problems with pharmacotherapy and result in negative healthcare outcomes. [13][14][15] According to Mathews and colleagues, the challenges of pharmaceutical communication with deaf patients goes beyond the difficulty of understanding these patients' needs and the challenge of learning basic skills in sign language.…”
Section: Introductionmentioning
confidence: 99%